New Trends and Issues on Fostering Collocation Competence of Chinese Language Learners: Innovation on Pedagogy, Methods and Analysis: Addressing New Challenges in Computer-Aided Chinese Language Teaching (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Along with the rapid development of computer and information technology, computer-aided language teaching has become a new trend in the development of foreign language teaching. They show the teaching content in multiple levels and in all directions, which is conducive to teachers' lectures and attracts students to actively participate and stimulate Learning interest has also brought about major changes in foreign language teaching materials, teaching methods and the entire teaching process. In addition to the great praise for multimedia-assisted Chinese teaching. On this course of learning and teaching, the new problem that arise should be addressed attentively in order to make it better for teaching.